Outcomes in Traumatic Brain Injury for Patients Presenting on Antiplatelet Therapy. Issue 2 (February 2015) - Cull, John David; Sakai, Lauren M.; Sabir, Imran; Johnson, Brent; Tully, Andrew; Nagy, Kimberly; Dennis, Andrew; Starr, Frederic L.; Joseph, Kimberly; Wiley, Dorion; Moore, Henry R.; Oliphant, Uretz J.; et al.
An increasing number of patients are presenting to trauma units with head injuries on antiplatelet therapy (APT). The influence of APTon these patients is poorly defined. This study examines the outcomes of patients on APT presenting to the hospital with blunt head trauma (BHT). Registries of two Level I trauma centers were reviewed for patients older than 40 years of age from January 2008 to December 2011 with BHT. Patients on APT were compared with control subjects. Primary outcome measures were in-hospital mortality, intracranial hemorrhage (ICH), and need for neurosurgical intervention (NI). Hospital length of stay (LOS) was a secondary outcome measure. Multivariate analysis was used and adjusted models included antiplatelet status, age, Injury Severity Score (ISS), and Glasgow coma scale (GCS). Patients meeting inclusion criteria and having complete data (n = 1547) were included in the analysis; 422 (27%) patients were taking APT. Rates of ICH, NI, and in-hospital mortality of patients with BHT in our study were 45.4, 3.1, and 5.8 per cent, respectively. Controlling for age, ISS, and GCS, there was no significant difference in ICH (odds ratio [OR], 0.84; 95% confidence interval [CI], 0.61 to 1.16), NI (OR, 1.26; 95% CI, 0.60 to 2.67), or mortality (OR, 1.79; 95% CI, 0.89 to 3.59) associated with APT. Subgroup analysis revealed that patients with ISS 20 or greater on APT had increased in-hospital mortality (OR, 2.34; 95% CI, 1.03 to 5.31). LOS greater than 14 days was more likely in the APT group than those in the non-APT group (OR, 1.85; 95% CI, 1.09 to 3.12). The effects of antiplatelet therapy in patients with BHT aged 40 years and older showed no difference in ICH, NI, and in-hospital mortality.